Be fruitful and multiply? Moderate fecundity and long-run reproductive success - Oded Galor; Marc Klemp (Brown University, Department of Economics, 2013)
This research presents the first evidence that moderate fecundity maximized long-run reproductive success within the human species. Exploiting an extensive genealogy record for nearly half a million individuals in Quebec during the seventeenth and eighteenth centuries, the study traces the number of descendants of early inhabitants in the subsequent four generations. Using the time interval between the date of marriage and the first live birth as a measure of reproductive capacity, the research establishes that while a higher fecundity is associated with a larger number of children, an intermediate level maximizes long-run reproductive success. The finding further indicates that the optimal level of fecundity was below the population median, suggesting that the forces of natural selection favored individuals with a lower level of fecundity. The research lends credence to the hypothesis that during the Malthusian epoch, natural selection favored individuals with a larger predisposition towards child quality, contributing to the onset of the demographic transition and the evolution of societies from an epoch of stagnation to sustained economic growth.
Keywords: J10; O10; 330; Demography; Evolution; Natural Selection; Fecundity; Quantity-Quality Trade-Off; Long-Run Reproductive Success